Monitoring Biosensors and Obtaining Data Using GSM Module - Hemavathy RM (Institute of Advanced Engineering and Science, 2016)
The main focus of the project is to prevent the loss of human life against the discomfort and death caused by the lack of attention towards the patients due to the improper monitoring systems provided in the hospital. The aim of the project is to monitor the bio sensors attached to the persons in their body either internally or externally. The biosensors which are about to be used in this project are EEG sensor (electro encephalogram sensor). An ECG sensor (electro cardiogram sensor) which is very essential for a critical patient, this project also emphasizes on the extended design of a special type of sensor called the oxygen insensitive microscale biosensor which helps in the monitoring of constant oxygen supply in blood thereby detecting blood cancer at the earliest stage. The data from all the sensors are sent to a central wireless node through wifi. From the main node the data is sent to the control station of the hospital through zigbee as the coverage area of certain hospitals is more than the coverage area of a Bluetooth. The control station segregates the data of different patients and stores in the memory location. If any of the patient data exceeds the standard data fed to the control station by the doctor then a message will be sent to the mobile of the attendee and the doctor using the GSM control system.Keywords: Biosensors, Raspberry pi (controller), GSM, Zigbee